Gefitinib (Iressa®®): a novel treatment for non-small cell lung cancer. Issue 1 (1st February 2004) - Vansteenkiste, Johan F
Current standard therapy for advanced or metastatic non-small cell lung cancer (NSCLC) includes chemotherapy, which is often associated with limited efficacy and toxicity. Thus, there is an unmet need for novel anticancer agents that are both effective and well tolerated in patients with NSCLC. Gefitinib (Iressa ®® ) is an orally active epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor in advanced clinical development, and the first agent of its kind to receive approval. Extensive evidence indicates that gefitinib provides significant antitumor activity in previously treated advanced NSCLC, along with fast symptom improvement. This orally administered agent is generally well tolerated. Gefitinib has also shown promising efficacy in other solid tumors that rely on EGFR-related mechanisms for growth and survival. This article reviews the profile of gefitinib and the evidence supporting its use in the treatment of NSCLC.